Water sources for red maple trees in a northern hardwood forest under a changing climate. Issue 8 (4th September 2020) - Harrison, Jamie L.; Blagden, Megan; Green, Mark B.; Salvucci, Guido D.; Templer, Pamela H.
Abstract: Climate models project increased growing season air temperatures and decreased depth and duration of winter snowpack for the north‐eastern United States, leading to greater frequency of soil freeze/thaw cycles in winter over the next century. We utilized the Climate Change Across Seasons Experiment (CCASE) at Hubbard Brook Experimental Forest in New Hampshire to determine how projected changes in climate in this region affect the depth from which trees take up water, which to our knowledge has yet to be determined. We determined the stable isotopic composition of water in soils and branch xylem three times throughout the growing season to partition potential sources of water for red maple ( Acer rubrum ) trees. Using a Bayesian mixing model approach, we determined that all trees used similar water sources in the early (June) and mid (July) growing season. However, in the late growing season (August), trees exposed to ambient and warmer growing season soil temperatures took up more than 40% of their water from between 90‐ and 100‐cm soil depth, likely due to greater water availability at this depth. In contrast, those trees exposed to soil freeze/thaw cycles in winter utilized water from all depths (0–100 cm) evenly (8–10%), possibly due to soil freezing causing compensatory root growth in the following growing season, compared with trees in the reference and warmed plots. These results demonstrate that the projected changes in climate for the north‐eastern United States are likely to alter the depth from which trees access water, especially in the late growing season.